Disruption of the gene Euchromatin Histone Methyl Transferase1 (Eu-HMTase1) is associated with the 9q34 subtelomeric deletion syndrome. Issue 4 (1st April 2005) - Kleefstra, T; Smidt, M; Banning, M J G; Oudakker, A R; Van Esch, H; de Brouwer, A P M; Nillesen, W; Sistermans, E A; Hamel, B C J; de Bruijn, D; Fryns, J-P; Yntema, H G; et al.
Abstract : Background: A new syndrome has been recognised following thorough analysis of patients with a terminal submicroscopic subtelomeric deletion of chromosome 9q. These have in common severe mental retardation, hypotonia, brachycephaly, flat face with hypertelorism, synophrys, anteverted nares, thickened lower lip, carp mouth with macroglossia, and conotruncal heart defects. The minimum critical region responsible for this 9q subtelomeric deletion syndrome (9q−) is approximately 1.2 Mb and encompasses at least 14 genes. Objective: To characterise the breakpoints of a de novo balanced translocation t(X;9)(p11.23;q34.3) in a mentally retarded female patient with clinical features similar to the 9q− syndrome. Results: Sequence analysis of the break points showed that the translocation was fully balanced and only one gene on chromosome 9 was disrupted— Euchromatin Histone Methyl Transferase1 ( Eu-HMTase1 )—encoding a histone H3 lysine 9 methyltransferase (H3-K9 HMTase). This indicates that haploinsufficiency of Eu-HMTase1 is responsible for the 9q submicroscopic subtelomeric deletion syndrome. This observation was further supported by the spatio-temporal expression of the gene. Using tissue in situ hybridisation studies in mouse embryos and adult brain, Eu-HMTase1 was shown to be expressed in the developing nervous system and in specific peripheral tissues. While expression is selectively downregulated in adult brain, substantial expression is retained in the olfactory bulb, anterior/ventral lateral ventricular wall, and hippocampus and weakly in the piriform cortex. Conclusions: The expression pattern of this gene suggests a role in the CNS development and function, which is in line with the severe mental retardation and behaviour problems in patients who lack one copy of the gene.